Investigating the effect of process parameters on dimensional accuracy and ultimate tensile strength of micro injection moulded micro parts - Mani, Mohammad Reza (2016)
This thesis presents two models for optimizing and guiding the micro injection moulding process. The models are generated by the use of a mathematical procedure, an understanding of the process, and empirical data obtained from several sets of experiments.